Sabda Bahagia sebagai Model Stress Coping Generasi Z: Dialog Kritis dengan Stoisisme - Bakhoh Jatmiko; Sherly Ester Ellain Kawengian; Teti Febriani Zega (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2026)
This study is motivated by the growing phenomenon of mental health problems experienced by Generation Z, which has contributed to the increasing popularity of Stoicism as a practical philosophy for stress coping among young people. This phenomenon raises theological questions regarding the adequacy of Stoicism when compared with Christian spirituality, particularly the teachings of Jesus in the Beatitudes or the Sermon on the Mount. This research employs a qualitative-descriptive method with a comparative theological analysis approach toward the concepts of happiness, emotions, suffering, virtue, and external realities in Stoicism and the Beatitudes. The findings reveal that both traditions share similarities in emphasizing virtue and rejecting external factors as the ultimate source of happiness. However, the study also finds that Stoicism emphasizes rational self-mastery and emotional detachment, whereas the teachings of Jesus offer a more holistic coping framework through spiritual reframing, emotional integration, identity formation as the people of God, emphasis on relationship with God, and eschatological hope. The novelty of this research lies in its recommendation of a Beatitudes-based stress coping model for Generation Z within pastoral theology and Christian spirituality, presenting a more comprehensive and transformative coping framework through the integration of psychological, relational, existential, and theological dimensions of human suffering.